Chromium Levels in Tobacco, Filter and Ash of Illicit Brands Cigarettes Marketed in Brazil. Issue 5 (27th January 2020) - Lisboa, Thalles Pedrosa; Mimura, Aparecida Maria Simões; da Silva, Julio Cesar Jose; de Sousa, Rafael Arromba
Abstract: Smoking is a public health problem and an important source of exposure to toxic metals. This work describes an efficient analytical method comparable to the ones based on atomic emission techniques for the determination of chromium in different constituent parts of cigarette samples (tobacco, filters and ashes) using electrothermal vaporization–atomic absorption spectrometry. The method was evaluated using 12 samples, and the results showed recovery values between 83 and 107%. The accuracy was also evaluated using a reference sample of tomato leaves (NIST SRM 1573a), which proved the efficiency of the method. The limits of detection of the developed method were 20.4, 75.8 and 80.7 ng g −1 for tobacco, filter and cigarette ash samples, respectively. The average chromium values found for the analyzed samples were in the range of 0.96 to 3.85 and from 0.32 to 0.80 μg/cigarette for tobacco and ashes, respectively. For most pre-burn and post-burn filter samples, the values of chromium concentration remained below limits of detection. The developed method presented adequate results about precision and accuracy, demonstrating its applicability in the determination of chromium in cigarette samples.